Best Practices for Recruiting and Retaining Fathers in Parenting Research: Insights from Fathering Researchers. - Deneault, Audrey-Ann; Feldman, Julia S.; Aytuglu, Alp; Bendel-Stenzel, Lilly C.; Olofson, Eric L.; Donithen, Reed; Schoppe-Sullivan, Sarah J.; Volling, Brenda L. (Parenting: Science & Practice)
SYNOPSIS: Objective. Significant progress has been made in studying and recognizing fathers' contributions to children's development. However, fathers remain underrepresented in parenting research relative to mothers. Logistical challenges are often cited as barriers to the successful recruitment, participation, and retention of fathers. The current study sought to better understand successful strategies to overcome barriers and include fathers in parenting research. Design. We conducted a qualitative study that utilized in-depth interviews with fatherhood scholars across the globe (N = 30) to identify (1) efficient practices for recruiting fathers and (2) effective strategies for retaining fathers in longitudinal research. We used thematic analysis to generate major and minor themes. Results. Six themes emerged, four related to successful recruitment practices (the composition of the research team; the location/method of recruitment; recruiting fathers, not parents; and being flexible with testing) and two related to challenges of recruiting fathers (mothers acting as gate-closers; the restrictions applied by some institutional research ethics boards). The analysis identified two successful retention practices: developing rapport with participating fathers and maintaining contact between waves of data collection. Conclusions. These themes provide insights into how to include fathers in parenting research successfully. Recommendations for conducting father-inclusive research are presented as well as best practices for including fathers in research.